Is Counterclockwise Rotation With Double Jaw Orthognathic Surgery Stable in the Long-Term in Hyperdivergent Class III Patients? - ERDEM, NECİP FAZIL; ACAR, YASEMİN BAHAR (W B SAUNDERS CO-ELSEVIER INC, 2018)
Purpose: To evaluate the long-term postsurgical stability of counterclockwise rotation of the occlusal plane (OP) in double-jaw orthognathic surgery in patients with hyperdivergent Class III malocclusion. Materials and Methods: This retrospective cohort study evaluated the postsurgical stability of orthognathic surgery in patients with skeletal Class III malocclusion and counterclockwise rotation of the maxillomandibular complex with an OP change of at least -2 degrees. Patients were evaluated with lateral cephalometric analysis before surgery, immediately after surgery, and at longest follow-up. The primary predictor variable was the change in angle of the OP and the Frankfort horizontal (FH) after surgery. The primary outcome variable was stability of the OP at longest follow-up. Other study variables were age, gender, and the following cephalometric measurements: mandibular plane angle; gonial angle; angle formed by the sella, nasion, and B point; maxillary height; angle of the palatal plane to the line connecting the sella and nasion; and distances of the posterior nasal spine and A point to the FH and of the A point to the vertical line passing from the nasion. The Mann-Whitney U test was used to compare stability between groups because the variables were not normally distributed. Bonferroni correction was used to evaluate P values. The chi(2) test and Fisher exact test, where appropriate, were used to compare the proportions of groups. A P value less than .05 was accepted as statistically significant. Results: The sample was composed of 15 adult patients (mean age at surgery, 23.5 yr; 40% men). The median duration of follow-up was 48 months (interquartile range, 36 to 60 months). The groups had similar demographic properties and similar surgical changes. Ten patients showed very stable results with an OP-FH change no greater than 1 degrees. Four patients showed unstable results with an OP-FH change of 2.25 +/- 0.5 degrees during the follow-up period. The change in the mandibular plane angle was notable between patients with stability and those with instability, which was the variable most affected by relapse of the OP. Conclusion: This study found long-term postsurgical skeletal stability of counterclockwise rotation of the OP during double-jaw orthognathic surgery in patients with high angle Class III malocclusion after a median follow-up of 48 months. (C) 2018 American Association of Oral and Maxillofacial Surgeons
Keywords: SKELETAL CLASS-III; OCCLUSAL PLANE ALTERATION; MAXILLOMANDIBULAR COMPLEX; CLOCKWISE ROTATION; MANDIBULAR AUTOROTATION; ADVANCEMENT SURGERY; STABILITY; AIRWAY; MALOCCLUSION; OSTEOTOMY